Differences in Calcium Clearance at Inner Hair Cell Active Zones May Underlie the Difference in Susceptibility to Noise-Induced Cochlea Synaptopathy of C57BL/6J and CBA/CaJ Mice - Liu, Hongchao; Peng, Hu; Wang, Longhao; Xu, Pengcheng; Wang, Zhaoyan; Liu, Huihui; Wu, Hao (Frontiers in Cell and Developmental Biology, 2021)
Noise exposure of a short period at a moderate level can produce permanent cochlear synaptopathy without seeing lasting changes in audiometric threshold. However, due to the species differences in inner hair cell (IHC) calcium current that we have recently discovered, the susceptibility to noise exposure may vary, thereby impact outcomes of noise exposure. In this study, we investigate the consequences of noise exposure in the two commonly used animal models in hearing research, CBA/CaJ (CBA) and C57BL/6J (B6) mice, focusing on the functional changes of cochlear IHCs. In the CBA mice, moderate noise exposure resulted in a typical fully recovered audiometric threshold but a reduced wave I amplitude of auditory brainstem responses. In contrast, both auditory brainstem response threshold and wave I amplitude fully recovered in B6 mice at 2 weeks after noise exposure. Confocal microscopy observations found that ribbon synapses of IHCs recovered in B6 mice but not in CBA mice. To further characterize the molecular mechanism underlying these different phenotypes in synaptopathy, we compared the ratio of Bax/Bcl-2 with the expression of cytochrome-C and found increased activity in CBA mice after noise exposure. Under whole-cell patch clamped IHCs, we acquired two-photon calcium imaging around the active zone to evaluate the Ca2+ clearance rate and found that CBA mice have a slower calcium clearance rate. Our results indicated that excessive accumulation of calcium due to acoustic overexposure and slow clearance around the presynaptic ribbon might lead to disruption of calcium homeostasis, followed by mitochondrial dysfunction of IHCs that cause susceptibility of noise-induced cochlear synaptopathy in CBA mice.